Coping Strategies and Coping Styles of Adolescents with Congenital and Acquired Disabilities (Cerebral Palsy, Oncology or Rheumatic Diseases Diagnosis) - Odintsova, M.; Sorokova, M.G. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2021)
The study aims to compare adolescents coping strategies and coping styles depending on their gender and health status. Sample was subdivided into 3 groups: 1) healthy, 2) adolescents with cerebral palsy (congenital disability), 3) adolescents with oncology and rheumatic diseases (acquired disability). The sample size is 244 adolescents from 13 to 18 years old. 86 healthy subjects (37 boys and 24 girls, M=15.03+1.39 y.o.), 61 with oncology of the brain and spinal cord (46 boys and 40 girls, M=14.96+1.52 y.o.), 46 with rheumatic diseases (17 boys and 29 girls, M=14.70+1.50 y.o.), and 51 with cerebral palsy (28 boys and 23 girls, M=15.30+1.17 y.o.). The R. Carver' COPE questionnaire, adapted by Ye.I. Rasskazova, T.O. Gordeyeva, Ye.N. Osin was used. It is found that adolescents with acquired disabilities use coping strategies similar to healthy peers, in contrast to adolescents with cerebral palsy, whose coping strategies are diverse. Adolescents in two clinical groups are more likely seeking support in religion than healthy ones, which reduces the stress impact by disability. Cognitively oriented coping styles is higher among healthy sample, emotionally oriented ones among adolescents with acquired disabilities, and dysfunctional ones among adolescents with cerebral palsy. Different trends in the intensity of coping strategies in clinical and healthy groups depending on gender are revealed. Целью данной работы стал сравнительный анализ копинг-стратегий и копинг-стилей подростков в зависимости от пола и группы: 1) здоровые; 2) подростки с детским церебральным параличом (врожденная инвалидность); 3) подростки с онкологией и ревматическими заболеваниями (приобретенная инвалидность). В исследовании приняли участие 244 подростка от 13 до 18 лет, из них 86 — здоровых подростков (46 мальчиков и 40 девочек, M=14,96+1,52 лет), 61 — с онкологией головного и спинного мозга (37 мальчиков и 24 девочки, M=15,03+1,39 лет), 46 — с ревматическими заболеваниями (17 мальчиков и 29 девочек, M=14,7+1,50 лет), 51 — с детским церебральным параличом (28 мальчиков и 23 девочки, M=15,3+1,17). Использовался опросник СОРЕ Р. Карвера в адаптации Е.И. Рассказовой, Т.О. Гордеевой, Е.Н. Осина. Обнаружено, что подростки с приобретенной инвалидностью используют схожие со здоровыми сверстниками копинг-стратегии в отличие от подростков с детским церебральным параличом, у которых копинг-стратегии вариативны. Подростки двух клинических групп чаще здоровых обращаются к религии, что смягчает воздействие стресса в условиях инвалидности. Процент подростков, предпочитающих когнитивно-ориентированный копинг-стиль, выше среди здоровых, эмоционально-ориентированный — среди подростков с приобретенной инвалидностью, а дисфункциональный копинг-стиль — среди подростков с детским церебральным параличом. Выявлены различные тенденции в выраженности копинг-стратегий в клинических и здоровой группах в зависимости от пола.